Exploring Traditional and Contemporary Sources of New Formations in Modern Russian - Sevinch, Izzatullaeva; Gulsevar, Alkhamova; Chingizovna, Radjabova Zamira (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
The article is devoted to neologization, which was studied by famous scientist-linguists as V.Vinogradov and V.M.Mokienko. The new words-neologisms in the Russian language are analysed by giving several examples in original language and in the English language. there are also new words compared in different periods, in this case, last century and current century. In particular, abbreviations in Russian are analysed in detail. Digital slang is given with appropriate and non-appropriate definitions in the local and other language’s dictionaries.